Molecular Dynamics Simulation Studies of Caffeine Aggregation in Aqueous Solution - Tavagnacco, Letizia (2011)
Molecular dynamics simulations were carried out on a system of eight independent caffeine molecules in a periodic box of water at 300 K, representing a solution near the solubility limit for caffeine at room temperature, using a newly-developed CHARMM-type force field for caffeine in water. Simulations were also conducted for single caffeine molecules in water using two different water models (TIP3P and TIP4P). Water was found to structure in a complex fashion around the planar caffeine molecules, which was not sensitive to the water model used. As expected, extensive aggregation of the caffeine molecules was observed, with the molecules stacking their flat faces against one another like coins, with their methylene groups staggered to avoid steric clashes. A dynamic equilibrum was observed between large n-mers, including stacks with all eight solute molecules, and smaller clusters, with the calculated osmotic coefficient being in acceptable agreement with the experimental value. The insensitivity of the results to water model and the congruence with experimental thermodynamic data suggest that the observed stacking interactions are a realistic representation of the actual association mechanism in aqueous caffeine solutions.